Partie orientale de la Nouvelle France ou du Canada avec l'Isle de Terre-Neuve et de Nouvelle Escosse, Acadie et Nouv. Angleterre avec Fleuve de St. Laurence : representé par Math. Seutter, geogr. de S. M. Imper. d'Augsbourg / Dressé par Alb. Charl. Seutter, Geogr. Tob. Conr. - Seutter, Albrecht Carl.; Seutter, Matthaeus, 1678-1756. http://id.loc.gov/authorities/names/n83052694 http://viaf.org/viaf/sourceID/LC|n83052694; Lotter, Tobias Conrad, 1717-1777. http://id.loc.gov/authorities/names/n50043414 http://viaf.org/viaf/sourceID/LC|n50043414 (UM Clark Library Maps, 1756)
Relief shown pictorially.; Includes decorative cartouche and ill. of ships. 1 map : hand col. 56 x 48 cm.